Stented valve dynamic behavior induced by polyester fiber leaflet material in transcatheter aortic valve devices. (October 2018) - Hatoum, Hoda; Heim, Frederick; Dasi, Lakshmi Prasad
Abstract: Objective: This study aims at assessing the global dynamic behavior, elastic deformability, closing energy and turbulence of rigid versus deformable stented (RS vs DS) valve systems with deformable and rigid textile materials (DT vs RT) through studying the stent-valve interaction compared to a bioprosthetic material in transcatheter aortic valves (TAV). Methods: Three 19 mm stented textile TAV designs (RS-DT, RS-RT and DS-RT) with different stent and leaflet properties were tested and compared with a control bioprosthetic TAV (RS-DB) in a left heart simulator flow loop under physiological pressure and flow. Particle Image Velocimetry and high speed imaging were performed. Pressure gradients (PG), leakage fractions (LF), Pinwheeling indices (PI), closing energy (E) and Reynolds shear stresses (RSS) were calculated. Results: (a) PGs and LFs were 11.86 ± 0.51 mmHg, 11.70 ± 0.34%; 8.84 ± 0.40 mmHg, 29.80 ± 0.76%; 11.59 ± 0.12 mmHg, 14.23 ± 1.64%; and 7.05 ± 0.09 mmHg, 12.08 ± 0.45% % for RS-DB, RS-DT, RS-RT and DS-RT respectively. (b) PIs were 15.79 ± 2.34%, 4.36 ± 0.84%, 2.47 ± 0.51% and 2.03 ± 0.33% for RS-DB, RS-DT, RS-RT and DS-RT respectively. (c) E is lowest for DS-RT (0.0010 ± 0.0002 J) followed by RS-RT (0.0017 ± 0.0002 J), RS-DB (0.0023 ± 0.0004 J) and highest with RS-DT (0.0036 ± 0.0007 J). (d) At peak systole lowest RSS was obtained with RS-DT (87.82 ± 0.58 Pa) and highest with DS-RT (122.98 ± 1.87 Pa). Conclusion: PGs, LFs, PIs and E were improved with DS-RT compared to other textile TAVs and RS-DB. Despite achieving more RSS than the rest of TAVs, DS-RT still falls within the same range of RSS produced by the other 2 valves and control exceeding the threshold for platelet activation. Graphical abstract: fx1 Highlights: Textile valves yield larger leakage than biological ones as they're porous. Deformable stent with rigid leaflets yields lowest pressure gradients and leakage. The more elastic stent provides better elastic deformability of the valve system. Energy involved in fabric deformation helps damping forces applied on valve-stent. RSS at peak systole fall in the same range regardless of valve nature.